Penyuluhan Kepada Orangtua Untuk Membimbing Anak Mampu Bersikap Asertif - Nofriza, Fatma; Semara Lakhsmi, Bety; Syafrida Nasution, Evi; Sari, Afrina (Media Abdimas, 2024)
Absrak Orangtua merupakan pendidik pertama dan utama dalam tumbuh kembang anak terutama anak usia dini. Di era generasi Z atau gen z sebahagian besar ahli mengatakan adalah generasi yang membutuhkan penguatan karakter agar anak tumbuh menjadi generasi kuat sesuai dengan zamannya. Oleh karena itu orangtua perlu memberikan penguatan karakter kepada anak untuk mampu memiliki sikap asertif. agar tumbuh jadi anak yang kuat , percaya diri dan jauh dari korban bullying. Sikap asertif merupakan sikap yang tegas dalam berkomunikasi dengan orang lain sesuai dengan keinginan dan pikirannya dan tanpa menyakiti orang lain. Tujuan dari pengabdian ini adalah melatih orangtua terutama ibu- ibu di desa wisata Margaluyu untuk membimbing anak memiliki sikap asertif. Metode yang digunakan adalah problem base learning, dan bermain peranan . Subjeknya adalah ibu â€“ ibu yang memiliki anak usia pra sekolah dan sd . Hasil kegiatan menunjukkan bahwa pengetahuan tentang membimbing anak untuk mampu bersikap asertif semakin meningkat dan mampu memberikan contoh contoh tentang sikap asertif yang perlu dilatihkan pada anak. Kegiatan yang dilakukan dapat memberi manfaat bagi para orangtua yang memiliki anak usia dini terdiri dari pra sekolah, dan sd yang rentan korban kejahatan. Abstract The role of parents as primary educators in the growth and development of children, particularly in early childhood, is widely acknowledged. In the current era marked by Generation Z, experts emphasize the importance of instilling strong character traits in children to ensure they develop into resilient individuals suited to the challenges of their time. One essential attribute is assertiveness, which equips children to navigate social interactions confidently and effectively, thereby reducing their vulnerability to bullying and other forms of victimization. Assertiveness is a firm yet respectful manner of communication that honors the perspectives and desires of others. Recognizing this imperative, efforts have been undertaken to equip parents, particularly mothers in the Margaluyu tourist village, with the necessary knowledge and skills to nurture assertiveness in their children. Utilizing problem-based learning and role-playing methodologies, mothers with preschool and elementary school-aged children have been engaged as participants. The focus of the training is to enhance parents’ understanding of assertiveness and equip them with practical strategies for fostering this trait in their children.The results of the training sessions indicate a notable increase in parental knowledge regarding the guidance of assertive behavior in children. Participants have demonstrated an ability to identify and exemplify assertive attitudes that warrant cultivation in their children. The implications of this study extend to parents who have young children (preschool and elementary school children) that susceptible to victimization.